Answer:
see explanation
Step-by-step explanation:
A recursive rule allows us to find the term in a sequence from the previous term.
From the given geometric sequence find r the common ratio
r =
=
= - 4
Hence recursive rule is
= - 4
( a₁ =
)
Answer:
its for sure C
Step-by-step explanation:
Answer:
6
-7
Step-by-step explanation:
simplyifying this we get
1+5i-8+i
= 6i-7
I am assuming the i you are talking about here is the sqrt of negative one so that would be 6
-7
17.
x = -2 is not a solution of -1 < x < 5 because -2 < -1 (-1 < -2 < 5 FALSE).
18.
m = 5 is a solution of 5 ≤ m because 5 ≤ 5 ( 5 ≤ m → m ≥ 5 greater than 5 or equal 5, 5 is equal 5)
19.
k = 10 is not solution of 2k - 3 < 1 because:
put the value of k to the inequality:
2(10) - 3 < 1
20 - 3 < 1
17 < 1 FALSE
1/2(4y+7)
Use the distributive property. a(b+c)= ab+ac
1/2*4y= 2y
1/2*7= 3.5
2y+3.5 <---- simplified expression
I hope this helps!
~kaikers